Walking speed declines with age in male and female baboons (Papio sp.): Confirmation of findings with sex as a biological variable. Issue 5 (10th August 2021) - Huber, Hillary F.; Gerow, Kenneth G.; Li, Cun; Nathanielsz, Peter W.
Abstract: We measured walking speed in baboons (67 female, 36 male; 5–22 years) to develop regression formulas to predict biological age. The final model strongly predicted age from just speed and sex. Walking speed is a valuable baboon aging biomarker. We present the first male speed data in a nonhuman primate.